Magnetic impurity states in simple metals: A study of the spin-polarization energy - P. Mavropoulos; N. Stefanou; N. Papanikolaou (PHYSICAL REVIEW B, 1998)
We report a systematic study of the spin-polarization energy of 3d impurities in monovalent simple-metal hosts, by means of self-consistent, local-spin-density-functional, impurity-in-jellium calculations, and propose a phenomenological model for the interpretation of our results. {[}S0163-1829(98)03424-9].